Randomized phase I clinical trial of anti–α‐synuclein antibody BIIB054. Issue 8 (17th June 2019) - Brys, Miroslaw; Fanning, Laura; Hung, Serena; Ellenbogen, Aaron; Penner, Natalia; Yang, Minhua; Welch, Mackenzie; Koenig, Erica; David, Eric; Fox, Tara; Makh, Shavy; Aldred, Jason; et al.
Abstract: Background: Pathological and genetic evidence implicates toxic effects of aggregated α‐synuclein in the pathophysiology of neuronal dysfunction and degeneration in Parkinson's disease. Immunotherapy targeting aggregated α‐synuclein is a promising strategy for delaying disease progression. Objective: This study (NCT02459886) evaluated the safety, tolerability, and pharmacokinetics of BIIB054, a human‐derived monoclonal antibody that preferentially binds to aggregated α‐synuclein, in healthy volunteers and participants with Parkinson's disease. Methods: A total of 48 healthy volunteers (age 40–65, 19 women) and 18 Parkinson's disease participants (age 47–75, 5 women, Hoehn and Yahr stage ≤2.5) were in the study. Volunteers were enrolled into 6 single‐dose cohorts of BIIB054 (range 1–135 mg/kg) or placebo, administered intravenously; Parkinson's disease participants received a single dose of BIIB054 (15 or 45 mg/kg) or placebo. All participants were evaluated for 16 weeks with clinical, neuroimaging, electrocardiogram, and laboratory assessments. Serum and cerebrospinal fluid BIIB054 concentrations were measured. BIIB054/α‐synuclein complexes were measured in plasma. Results: Most adverse events were mild and assessed by investigators as unrelated to the study drug. Pharmacokinetic parameters for volunteers and the Parkinson's disease participants were similar. BIIB054 serum exposure and maximum concentrations were dose proportional during the dose range studied. In volunteers and the Parkinson's disease participants, the serum half‐life of BIIB054 was 28 to 35 days; the cerebrospinal fluid–to‐serum ratio ranged from 0.13% to 0.56%. The presence of BIIB054/α‐synuclein complexes in plasma was confirmed; all Parkinson's disease participants showed almost complete saturation of the BIIB054/α‐synuclein complex formation. Conclusions: BIIB054 has favorable safety, tolerability, and pharmacokinetic profiles in volunteers and Parkinson's disease participants, supporting further clinical development. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.